Through interface design, enhancing communication and promoting a shared understanding amongst meeting participants of formally structured remote meetings - Nyström, Malin; Ottersten, Hedda (My University, 2016)
Remote collaboration has become a greater part of today’s workplaces, making it possible to put together specialized teams that are geographical distributed in a cost saving way. This primarily due to being able to communicate through technology such as videoconferencing systems. Although, despite the growing popularity for conducting meetings remotely it is difficult to match the fullness that face-to-face meeting brings. Compared to physical meetings there are several factors which inhibits remote meetings to rise to its full potential, having a negative impact on the joint understanding for meeting content as well as meeting participants understanding for one another. Thus, the overall aim of this study is to contribute with research within the field of remote collaboration, having communication between remote sites as a focal point. The primary focus lies upon on how to enhance communication and promote a shared understanding across meeting participants The MERCO-project (Mediated Effective Remote Collaboration) lays as the base for this study, where our fields of responsibility in involved conducting a preliminary study and creation of all prototypes. During this process both usability tests and heuristic evaluations were performed. Furthermore, the fruit of this study is an interactive mockup where the functions and features are evaluated and discussed in relation to the five media characteristics promoted by the Media Synchronicity Theory, and how convergence may be obtained. Conclusively, whether communication is enhanced and a shared understanding promoted are dependent mainly on three prominent factors; equivocality and uncertainty, group establishment and employee hierarchy. The MERCO-project was conducted on behalf of Ericsson AB, Semcon AB, Chalmers university of Technology, ETH, AVS, Intelliconcept and Touchtech.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction